Insuring against private capital flows: is it worth the premium? ; What are the alternatives? - Jörg Bibow (Levy Economics Institute of Bard College, 2008)
Following an analysis of the forces behind the global capital flows paradox observed in the era of advancing financial globalization, this paper sets out to investigate the opportunity costs of self-insurance through precautionary reserve holdings. We reject the idea of reserves as low-cost protection against the vagaries of global finance. We also deny that arrangements giving rise to their rapid accumulation might be sustainable in the first place. Alternative policy options open to developing countries are explored, designed to limit both the risks of financial globalization and the costs of insurance-type responses. We propose comprehensive capital account management as an alternative to full capital account liberalization. The aims of a permanent regulatory regime of capital controls, with respect to both the aggregate size and the composition of capital flows, are twofold: first, to maintain sufficient macro policy space; second, to assure a good micro fit of external expertise incorporated in foreign direct investment as part of a country's development strategy.
Keywords: E43; E58; F02; F32; F33; F55; 330; International monetary order; financial globalization; capital flows; financial crises; capital controls; foreign reserves